PENINGKATAN PRESTASI BELAJAR SISWA PADA PEMBELAJARAN AL-QUR’AN HADITS MATERI AL-SYAMSIAH DAN AL-QOMARIAH DENGAN MEDIA AUDIO VISUAL DI KELAS III SEMESTER 2 MI SALAFIYAH KEBARONGAN TAHUN PELAJARAN 2016/2017 - Siti Fatimah (Pusat Studi Pendidikan dan Kreativitas Guru, 2020)
This research is motivated by the teacher in delivering learning materials using only the lecture method. With this lecture method students do not experience direct learning but memorize. This study is intended to answer the following problems: 1) How can the learning process using audio-visual media with VCD increase the attention, activeness, and learning outcomes of students in learning Al-Qur ’an Hadith for grade III Semester 2 students of MI Salafiyah Kebarongan in the 2016/2017 academic year? This problem is discussed through classroom action research which is carried out in 2 cycles with each cycle of stages being planning, acting, observing and reflecting. The research data is obtained through classroom observations and documentation of the results of the actions taken as well as data about the description, with this action research it will be known that the increase or decrease after the classroom action is carried out per cycle. This study shows that: 1) Learning using audio- visual media can increase students’ attention in learning Al Qur ’an Hadith reaching 96.15%. 2) Learning using audio visual media can increase student activeness in learning Al Qur ’an Hadith which reaches 90%. 3) Learning using audio-visual media can improve student learning outcomes which is marked by the achievement of student learning completeness reaching 81, 92%.